2003
DOI: 10.1124/dmd.31.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inactivation of Cytochrome P450 2B6 by a Novel Terminal Acetylene Inhibitor

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:N-(3,5-Dichloro-4-pyridyl)-3-(cyclopentyloxy)-4-methoxybenzamide (DCMB) is a known marker substrate for cytochrome P450 2B6. Based on the chemical template of DCMB, a novel terminal acetylene compound, N-(3,5-dichloro-4-pyridyl)-4-methoxy-3-(prop-2-ynyloxy)benzamide (TA) was synthesized and evaluated as a mechanism-based inactivator of P450 2B6. The pseudo first-order inactivation of expressed P450 2B6 by TA was both substrate and time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…This is an electrophilic and highly reactive molecule which may or may not be the heme-alkylating species, but it is stable enough to leave the enzyme and cause major cellular damage by binding covalently to nucleophilic sites in proteins and even nucleic acids (see Part 5). [140]. Among positional isomers, a CC bond in a propynyl group (RÀCCÀCH 3 ) appears as reactive as a terminal ethynyl group in beeing activated to an inhibitory species.…”
Section: Fig 253mentioning
confidence: 99%
“…This is an electrophilic and highly reactive molecule which may or may not be the heme-alkylating species, but it is stable enough to leave the enzyme and cause major cellular damage by binding covalently to nucleophilic sites in proteins and even nucleic acids (see Part 5). [140]. Among positional isomers, a CC bond in a propynyl group (RÀCCÀCH 3 ) appears as reactive as a terminal ethynyl group in beeing activated to an inhibitory species.…”
Section: Fig 253mentioning
confidence: 99%
“…The reaction product, 4-hydroxymephenytoin, was detected and quantified by high-performance liquid chromatography/ mass spectrometry as previously described (Fan et al, 2003). Sample areas were read from a linear regression of known standards (range, 4.68 -150.00 pmol) using 1/ϫ weighting.…”
Section: Methodsmentioning
confidence: 99%
“…The conversion of diclofenac (20-M final assay concentration) to 4-hydroxydiclofenac was used to measure CYP2C9 metabolic activity in individual microsomal preparations. The product, 4-hydroxydiclofenac, was separated and quantified by high-performance liquid chromatography using a previously described method (Fan et al, 2003). Sample areas were read from a linear regression of known standard amounts (range, 40 -5000 pmol) using no weighting.…”
Section: Methodsmentioning
confidence: 99%
“…TDI is an unusual occurrence with most enzymes, but it is observed at a higher frequency in P450-catalyzed reactions, perhaps due to the reactivity of the oxygenated species formed during the course of the oxygenation reactions (Hollenberg, 2002). There are examples of irreversible or quasi-irreversible P450 inhibition across many classes of therapeutic drugs, recreational drugs, and herbal medicines (Zhou et al, 2005), and all of the major drug-metabolizing P450s have been implicated (Kunze and Trager, 1993;Lopez-Garcia et al, 1994;Newton et al, 1995;Koenigs and Trager, 1998; Chun et al., 2001a,b;Ha-Duong et al, 2001;Palamanda et al, 2001;Bertelsen et al, 2003;Fan et al, 2003;Lu et al, 2003;Polasek et al, 2004;Zhou et al, 2004).In a drug discovery setting, three different analytical endpoints are typically used for the study of P450 inhibition in vitro: liquid scintillation counting of radioactivity liberated during site-specific metabolism (Moody et al, 1999), selective analysis of fluorescent metabolites (Crespi and Stresser, 2000), and mass spectrometry (Yin et al,Article, publication date, and citation information can be found at …”
mentioning
confidence: 99%